THE INFLUENCE OF BEAUTY VLOGGER, ONLINE CUSTOMERREVIEWAND IMPULSE BUYING DECISIONS, ON INTEREST TO BUY ONLINE ON SOMETHINC SKINCARE PRODUCTS (Case study on students of the Faculty of Economics and Business of Universitas Malikussaleh ) - Zikra; Jullimursyida; M.Subhan; Chalirafi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study aims to test the influence of beauty vloggers, online customer reviews and impulse buying decisions on online purchasing interest in Somethinc skincare products (case study on students of the Faculty of Economics and Business, Malikussaleh University). The number of respondents in this study was 100 respondents.at the Faculty of Economics and Business, Malikussaleh University. The data analysis method used is Multiple Linear Regression with SPSS Software. The results of this study found that Somethinc Beauty vlogger skincare directly has a significant effect on online purchasing interest in Somethinc skincare products online. This shows that beauty vloggers influence purchasing interest. Thus, beauty vloggers are included in the considerations that consumers prioritize in attracting purchasing interest on Shopee, Instagram, and TikTok shops. Online customer reviews do not have a significant effect on online purchasing interest in Somethinc skincare products. Thus, online customer reviews are not included in the considerations that are prioritized in increasing purchasing interest, so that positive and negative reviews are not the main stimulus in creating purchasing decisions. This shows that online customer reviews do not affect purchasing interest in the Instagram, TikTok Shop, Shopee applications, if the reviews given are increasingly positive, purchasing interest does not necessarily increase. Impulse buying decisions have a positive and significant effect on online purchasing interest in Somethinc skincare products. Thus, impulse buying decisions are included in the considerations that are prioritized in increasing purchasing interest.